Plasmapheresis leading to remission of refractory nephrotic syndrome due to fibrillary glomerulonephritis: a case report - Pliquett Rainer U; Mohr Peter; El Din Mukhtar Badr; Girndt Matthias; Markau Silke (Journal of Medical Case Reports, 2012)
Abstract Introduction Fibrillary glomerulonephritis (FibGN) is characterized by extracellular deposition of Congo red-negative microfibrils within the glomerular mesangium and leads to gross proteinuria or nephrotic syndrome. After diagnosis of FibGN, end-stage renal disease occurs within four years in 50% of patients. Case presentation A 36-year-old Caucasian woman with proteinuria and intermittent nephrotic syndrome due to FibGN intermittently received immunosuppressive therapies, including glucocorticoids, mycophenolate mofetil, and rituximab, for 10 years. However, disease remission was not achieved and progressive kidney injury developed. Ultimately, in stage IV of chronic kidney disease (Kidney Disease: Improving Global Outcomes), three cycles of plasmapheresis of five to seven sessions each were performed every three to four months, reducing steady-state proteinuria from 7 to less than 1 g/day. Here, plasmapheresis led to a remission of nephrotic syndrome associated with FibGN. Conclusions Plasmapheresis therapy is proposed as a further option for immunosuppressant-refractory FibGN.